Peningkatan hasil belajar SBdP melalui metode demonstrasi pada materi seni kolase dikelas IV - Salempa, Bernike Pi’tuk (Global Journal Teaching Professional, 2023)
The problem in this research is whether the demonstration learning method can improve the learning outcomes of fourth-grade students in the SBdP subject with collage art material? The objective of this research is to improve the learning outcomes of fourth-graders in the SBdP subject with collage art material of School SDN 3 BUNTAO’. The type of classroom action research is carried out in two steps, while the steps in this research include the planning, action implementation, observation, and reflection. The data obtained in this research include student learning outcomes, teacher activity observations, and student activity observation sheets. The results showed that in the first cycle of action, the percentage of classical learning mastery was 44,4% but the learning outcomes had not reached 75%, so it was continued in the second cycle. In the action of implementing the second cycle, the percentage of learning completeness wa 92,5%, 25 students completed the 27 students who took the test. The results of observations of teacher activities increased from 58.57% in the first cycle to 82.8%. Student activity increased 60% in the first cycle to 83.3% in the second cycle. Thus, it can be concluded that the demonstration method can improve student learning outcomes in subjects such as collage art material to Fourth Grade Students of SDN 3 BUNTAO’. Permasalahan dalam penelitian ini yaitu apakah metode pembelajaran demonstrasi dapat meningkatkan hasil belajar siswa kelas IV pada mata pelajaran SBdP dengan materi seni kolase? Tujuan penelitian untuk meningkatkan hasil belajar siswa kelas IV pada mata pelajaran SBdP dengan materi seni kolase di SDN 3 BUNTAO’. Jenis penelitian tindakan kelas (PTK) yang dilaksanakan dalam dua tahap, adapun tahapan dalam penelitian ini meliputi tahap perencanaan, pelaksanaan tindakan, observasi dan refleksi. Data yang diperoleh dalam penelitian ini meliputi hasil belajar siswa, hasil observasi aktivitas guru, dan hasil observasi aktivitas siswa. Hasil penelitian menunjukkan bahwa pada tindakan siklus I diperoleh presentase ketuntasan belajar klasikal sebesar 44,4% namun hasil belajar tersebut belum mencapai KKM 75% maka dilanjutkan pada siklus II. Pada tindakan pelaksanaan siklus II diperoleh presentase ketuntasan belajar 92,5% terdapat 25 siswa yang tuntas dari 27 siswa yang mengikuti tes. Hasil observasi aktivitas guru meningkat dari 58,57% pada siklus I menjadi 82,8%. Aktivitas siswa meningkat 60% pada siklus I menjadi 83,3% pada siklus II dengan demikian dapat disimpulkan bahwa melalui metode demonstrasi dapat meningkatkan hasil belajar siswa pada mata pelajaran SBdP materi seni kolase di kelas IV SDN 3 BUNTAO’.